Worlds Apart in Acadie: Official Languages Programs in Education in New Brunswick and Nova Scotia, 1968-1984 - Hayday, Matthew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2002)
AbstractFollowing the recommendations of the Royal Commission on Bilingualism and Biculturalism, the Canadian and provincial governments undertook a wide array of measures to promote Canada's two official languages through education programs. Over the fifteen years following the passage of the Official Languages Act, minority and second official-language education programs developed in a markedly different fashion in the two provinces with the largest Acadian communities: New Brunswick and Nova Scotia. A combination of factors, including the demographic weight of the Acadian communities, the strategies of Acadian lobby groups, the attitudes of the majority and minority communities, and the ideologies of key politicians and civil servants must all be taken into account to explain the uneven development of official language education programs in these two “Acadian provinces”.